2004
DOI: 10.1111/j.1523-1755.2004.66017.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and survival on dialysis in west London

Abstract: Indo-Asian and Afro-Caribbean hemodialysis patients have survival comparable to Caucasians despite a higher burden of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(11 reference statements)
1
9
1
Order By: Relevance
“…Our study showed that Caucasoid patients had significantly inferior survival compared to other ethnicities, consistent with other similar UK studies [18]. This trend for increased mortality in Caucasoids has also been demonstrated in the USA where socioeconomic and nutritional factors would be expected to have greater influence [19], and Wolf et al [20] hypothesised that higher use of activated vitamin D sterols in non-Caucasoids may offer a survival advantage.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our study showed that Caucasoid patients had significantly inferior survival compared to other ethnicities, consistent with other similar UK studies [18]. This trend for increased mortality in Caucasoids has also been demonstrated in the USA where socioeconomic and nutritional factors would be expected to have greater influence [19], and Wolf et al [20] hypothesised that higher use of activated vitamin D sterols in non-Caucasoids may offer a survival advantage.…”
Section: Discussionsupporting
confidence: 80%
“…This trend for increased mortality in Caucasoids has also been demonstrated in the USA where socioeconomic and nutritional factors would be expected to have greater influence [19], and Wolf et al [20] hypothesised that higher use of activated vitamin D sterols in non-Caucasoids may offer a survival advantage. That aside, it remains unclear as to why ethnic minorities have a survival advantage, although more elderly Caucasoids have underlying generalised atherosclerotic disease [18]. …”
Section: Discussionmentioning
confidence: 99%
“…No survival analysis reported due to small sample size. Relevant confounders were collected and included in analysis.Male: 44Female: 37Age 10-79Prasad, 2004 [46]Cohort study465Afro-Caribbean vs. South Asians vs. WhitesUnited KingdomClinic or hospital based studyNo limitation stated. Statistical methods vaguely described.Male: 288Female: 177DM unspecifiedRiste, 2001 [47]Cross-sectional study1,022Afro-Caribbean vs.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies investigated disparities in micro-vascular and macro-vascular complications among persons with diabetes [13,14,19,24,27,33,34,37,39,40,45,46,48]. The micro-vascular complications included retinopathy, nephropathy as well as peripheral sensory neuropathy or was not individually specified in the papers reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…It is however encouraging that studies conducted in both the UK and the United States report that survival rates in ESRD are not compromised due to ethnicity. In fact, several studies have reported better survival rates in South Asian dialysis patients [31, 32, 33, 34]. Although the determinants of better survival in South Asians are not fully understood, factors such as higher mean Kt/V have been associated with more favourable outcomes [34].…”
Section: Prevalence Of Esrd In South Asiansmentioning
confidence: 99%